Effect of early oral feeding on plasma free fatty acid concentrations in patients in a coronary care unit. Issue 7 (July 1975) - Opie, L H; Bruyneel, K J; Kennelly, B M
Abstract : Forty-two consecutive patients with acute myocardial infarction were studied over the first 3 days of their illness to determine the effect of oral or intravenous calorie intake on the circulating free fatty acid values. Repeated sampling in 9 patients showed that free fatty acid levels above 1000 mumol/l were seldom found beyond the first 10 hours after admission. Oral calories, chiefly in the form of carbohydrate, reduced free fatty acid by an average of 145 mumol/l for each intake of 90 or more calories (378kF) on the first day. Oral calories (especially carbohydrate) should be considered as possible antilipolytic therapy if it be held desirable to reduce circulating free fatty acid concentrations in patients with acute mycoardial infarction.